Seminar volume of the second European Doctoral Seminar (EDS): Bamberg, Germany, June, 4th - 6th, 2002 - Heinz-Dieter Wenzel; Stefan Hopp (Bamberg University, Bamberg Economic Research Group on Government and Growth (BERG), 2003)
TABLE OF CONTENTS: Preface - I. DEVELOPMENT ECONOMICS - 1. GUNTHER GRATHWOHL: The Macroeconomic Structure of Less Developed Countries ... 3 - II. RESEARCH ON THE ALBANIAN ECONOMY - 2. ARJETA ABAZI: Albania and its Monetary Transmission Mechanism ... 27 - 3. DORIANA DERVISHI: The Countries of Region and the Challenge of Economic Integration ... 35 - 4. ERMELINDA FEJZULLA: A Review of the Controversies and Evaluation Approaches on the International Monetary Fund's Supported Programs .. 43 - 5. ARSENA GJIPALI: Emigration and its Economic Consequences; the Transition Phase of Albania ... 63 - 6. ELIDA LIKO: Exchange Rate Variability and Policy Implication ... 71 - 7. SUELA THIMO: The Increase of Competition: an Important Factor for a Successful Transition ... 83 - III. RESEARCH ON OTHER TRANSITION ECONOMIES - 8. DOBRICZA ANIKÓ: A Debt Rate Paradox: Why is home financing not as effective as it was thought to be? ... 97 - 9. DŽENAN DONLAGIC: Monetary Policy in Bosnia and Herzegovina – Currency Board Arrangement ... 105 - 10. ADNAN EFENDIC: Specifics of Transition Process in BiH – Framework of Development Strategy for BiH ... 111 - Seminar Participants ... 119 - Seminar Program ... 123
Keywords: 330; Übergangswirtschaft; Albanien; Südosteuropa